If 2 is the zero of the polynomial then p (x)= 2x2-3x+7 a then a = _
Answers
Answered by
2
Step-by-step explanation:
Given polynomial p(x)=2x
2
−3x+7a is zero polynomial if x is 2
Replace x by 2 we get
∴2(2)
2
−3(2)+7a=0
⇒2×4−3×2+7a=0
⇒8−6+7a=0
⇒2+7a=0
Add -2 both sides we get
2+7a−2=0−2
⇒7a=−2
Divided by 7 both side we get
a=−
7
2
So a=−
7
2
Answered by
4
Step-by-step explanation:
hope it helped
Mark as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d6c/50f686104933ccc160f1140e5c98cc78.jpg)
Similar questions